To solve the equation \(4.8(x - 3.75) = -14.4\), we can follow these steps:
-
Distribute 4.8: \[ 4.8x - 4.8 \times 3.75 = -14.4 \] First, calculate \(4.8 \times 3.75\): \[ 4.8 \times 3.75 = 18 \] Now, substitute back into the equation: \[ 4.8x - 18 = -14.4 \]
-
Add 18 to both sides: \[ 4.8x = -14.4 + 18 \] Calculate \(-14.4 + 18\): \[ -14.4 + 18 = 3.6 \] Now, the equation becomes: \[ 4.8x = 3.6 \]
-
Divide by 4.8: \[ x = \frac{3.6}{4.8} \] To simplify \( \frac{3.6}{4.8} \): \[ x = \frac{3.6 \div 4.8}{4.8 \div 4.8} = \frac{0.75}{1} = 0.75 \]
So the solution is: \[ \boxed{0.75} \]